Partial oxidation of propane with CO2 on Ru doped catalysts. Issue 14 (6th April 2016) - Pradhan, Sivaram; Upham, David C.; Metiu, Horia; McFarland, Eric W.
Abstract : The catalytic activity and stability of Ru doped CeO2 and Ru doped ZrO2 are investigated and compared for the partial oxidation of propane using carbon dioxide as an oxidant. Abstract : The catalytic activity and stability of Ru doped CeO2 and Ru doped ZrO2 are investigated and compared for the partial oxidation of propane using carbon dioxide as an oxidant. On both the reducible Ru doped ceria and the irreducible Ru doped zirconia catalysts, the major products of propane partial oxidation were CO and H2 when CO2 is used as an oxidant, and the two catalysts had comparable activity below 450 °C. In addition to dry reforming products, the Ru doped CeO2 produced small quantities of methane above 450 °C. Neither catalyst showed measurable selectivity for oxidative dehydrogenation activity of propane-to-propylene with CO2 or CO. Coke formation will limit the utility of either catalyst for dry reforming of propane in practice.